2020
DOI: 10.3390/ma13214856
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Asymmetrically Functionalized Titania Nanoparticles into Nanoshells

Abstract: Titania (anatase) nanoparticles were anisotropically functionalized in water-toluene Pickering emulsions to self-assemble into nanoshells with diameters from 500 nm to 3 μm as candidates for encapsulation of drugs and other compounds. The water-phase contained a hydrophilic ligand, glucose-6-phosphate, while the toluene-phase contained a hydrophobic ligand, n-dodecylphosphonic acid. The addition of a dilute sodium alginate suspension that provided electrostatic charge was essential for the self-limited assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The self-assembly approach is widely used for the competitive surface assimilation of incompatible ligands, such as hydrophobic and hydrophilic ligands, on particle surfaces and for block copolymer formation, including di- and tri-block copolymers as summarized in Figure 7 [ 56 , 57 , 58 ]. Gold nanocrystals with their thiol-binding affinity are widely used to perform competitive adsorption of incompatible ligands onto particles via self-assembly [ 59 ].…”
Section: Fabrication Of Janus Particlesmentioning
confidence: 99%
“…The self-assembly approach is widely used for the competitive surface assimilation of incompatible ligands, such as hydrophobic and hydrophilic ligands, on particle surfaces and for block copolymer formation, including di- and tri-block copolymers as summarized in Figure 7 [ 56 , 57 , 58 ]. Gold nanocrystals with their thiol-binding affinity are widely used to perform competitive adsorption of incompatible ligands onto particles via self-assembly [ 59 ].…”
Section: Fabrication Of Janus Particlesmentioning
confidence: 99%
“…3 nm colloidal titania [ 33 ], (ii) ca. 10 nm hydrothermally synthesized titania [ 34 ], and (iii) molecular ammonium oxo-lactato titanate as sources [ 35 ] of titania dispersed in cellulose nanofibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Svensson et al in their communication, reported a proof of principle for the self-assembly of titania nanoshells from anisotropically functionalized titania NPs successfully utilized for fast-release drug delivery application [ 12 ].…”
mentioning
confidence: 99%